AB0979 A Comparison of Physical and Joint Ultrasonography Findings of The MTP Joint in Rheumatoid Arthritis. (15th July 2016) - Kashiwagura, T.; Kimura, Y.; Wakabayashi, I.; Yuasa, Y.; Miyamoto, S.; Kobayashi, M.; Sugimura, Y.; Miyakoshi, N.; Shimada, Y.
Abstract : Background: Rheumatoid arthritis (RA) causes a variety of foot lesions, but the feet and ankles are not included in disease activity indices such as the Disease Activity Score (DAS). The spread and usefulness of joint ultrasonography in RA diagnosis and treatment have recently been reported. Many disease activity indices use tender (painful) joints and swollen joints, but few reports have examined the association between synovitis on joint ultrasonography and physical findings. This study evaluated joint ultrasonography of the metatarsophalangeal (MTP) joint in RA patients and examined the results in conjunction with physical findings. Objectives: This study evaluated joint ultrasonography of the metatarsophalangeal (MTP) joint in RA patients and examined the results in conjunction with physical findings. Methods: The subjects were 65 RA patients (82 feet) visiting our department on an outpatient basis. Surgical patients were excluded. Their mean age was 64.1 (27–84) years, and the disease stage was Stage I in 19 subjects, II in 11 subjects, III in 10 subjects, and IV in 25 subjects. The degree of functional disability according to the Steinbrocker classification was Class I in 45 subjects, Class II in 16 subjects, and Class III in four subjects. Disease activity according to the DAS28-ESR was complete response in 16 subjects, low disease activity (LDA) in 27 subjects, moderate disease activity in 14 subjects, and high disease activity in 7 subjects. Twenty-two subjects were taking a combination of biological agents. After interviewing subjects about any foot-related complaints, pain and swelling were evaluated, and joint ultrasonography was performed. The same examiner examined all subjects in the same room using the same diagnostic equipment. Grade 1 or higher on power Doppler ultrasonography was defined as synovitis. Results: The detection rates of pain, swelling, and synovitis in all 410 toes were 33.9%, 14.1%, and 13.4%, respectively. Forefoot-related complaints were cited in 13 feet, and pain was observed in all subjects. However, synovitis was only detected in 38.5%, and many cases had asymptomatic synovitis. The detection rates of synovitis in subjects taking biological agents and subjects not taking biological agents were 11.0% and 24.4%, respectively, with no significant difference (Pearson's chi-squared test). When examined according to disease activity, synovitis was observed in 27.9% of those with LDA or less, which was the treatment objective. During the evaluations, joint swelling had to be differentiated from edema in a large number of cases. Conclusions: Out of pain, swelling, and synovitis, the detection rate was highest for pain. This was likely due to the inclusion of pain other than that from arthritis, such as from subluxation and dislocation of the MTP joint and plantar calluses. There was a high prevalence of asymptomatic synovitis, suggesting the utility of evaluating synovitis by joint ultrasonography. Acknowledgement: The authors thank Miss Sasaki, for her assistance with this project. Disclosure of Interest: None declared